Exploring communication competencies in accounting education: A thematic analysis - Buitendag, Natasha (Journal for Language Teaching, 2025)
In the accounting field, the development of chartered accountants should go beyond technical training. Given the ongoing changes in the industry, greater attention needs to be directed towards cultivating non-technical skills in this profession. The skills development prospective chartered accountants receive at tertiary level is mainly focused on the technical skills required during their practical training at their training firms. Their non-technical skills once they graduate, even though incorporated at tertiary level, are not at the level expected by their new employers. This study focused on communication skills as a non-technical incorporation into the accounting degree. The objective of this study was to discern whether newly graduated accounting students were equipped with the communication skills required to add value to their training at an accredited training firm. A case study approach was selected for this study, where recently graduated accounting students were interviewed to understand whether the communication skills incorporated in their degrees had been effectively developed and applied to enhance their professional performance in the early stages of their careers. The research revealed that teaching communication skills would have a longer-lasting impact on the students when included at a later stage in their studies and that a specific focus on presentation skills and real-life simulations would be of value.